Effect of biofertilizers, fertility level and weed management on weed growth and yield of late sown chickpea (Cicer arietintrm) - SINGH, RAJESH KUMAR; SHUKLA, D N; DE, NIRMAL (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted during winter (rabi) season of 2000-01 and 2001-02 at the Agriculture Research Farm of Institute of Agriculture Science, Banaras Hindu University, Varanasi, integrating biofertilizers, fertility levels and weed management to minimize weed interference for higher yield of late sown chickpea (Cicer arientium L.). The fertility levels and biofertilizers applied to chickpea caused significant effect on the weed population, biomass and seed yield but no effect onyseed protein content. Application of VAM alone was at par to inoculation of Ahizohium exhibited significantly lower weed population, dry matter accumulation and seed yield that the dual application of Rhizobium and VAM. Decreasing levels of fertility from 125 to 75% of recommended NPK dose exerted significantly marked reduction in population and dry matter ofweeds and increased in seed yield by 0.43 tonnesiha. f re-emergence application of pendimethalin 0.5 kg aiha coupled with 1 hoeing at 40 days after sowing significantly reduced the density and dry matter of weeds which resulted in 16% higher seed yield over weedy check condition.